Canadian Teachers’ Emotional Experiences during COVID-19: A Narrative Inquiry - Wells, Kendra; Daniels, Lia M. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
This narrative inquiry study delves into the emotional experiences of teachers during the COVID-19 pandemic, using restorying (Connelly & Clandinin, 1990) as a primary data analytic approach. Drawing on terror management theory, theories of emotional coping, broaden-and-build theory, and theories of emotion regulation, this study explores teachers’ emotional responses to challenges brought on by the pandemic. We interviewed three elementary school teachers in Alberta, Canada. The resultant three restoried narratives reveal a spectrum of emotions, from uncertainty and anxiety to curiosity and empathy, as teachers grappled with shifting job demands, social disconnection, and feelings of inadequacy. The discussion highlights the importance of understanding teachers’ emotions in the context of broader theoretical frameworks by providing multiple theoretical avenues for understanding the emotions in the narratives. Implications of the study underscore the need for administrators to listen to teachers’ stories and for researchers to explore narrative inquiry as a therapeutic process.